Color tunability of intense upconversion emission from Er3+-Yb3+ co-doped SiO2-Ta2O5 glass ceramic planar waveguides - Ferrari, Jefferson Luis; Lima, Karmel de Oliveira; Pecoraro, Édison [UNESP]; Ferreira, Rute A. S.; Carlos, Luis D.; Goncalves, Rogeria Rocha (Royal Soc Chemistry, 2012)
This work reports on the infrared-to-visible CW frequency upconversion from planar waveguides based on Er3+-Yb3+-doped 100-xSiO(2)-xTa(2)O(5) obtained by a sol-gel process and deposited onto a SiO2-Si substrate by dip-coating. Surface morphology and optical parameters of the planar waveguides were analyzed by atomic force microscopy and the m-line technique. The influence of the composition on the electronic properties of the glass-ceramic films was followed by the band gap ranging from 4.35 to 4.51 eV upon modification of the Ta2O5 content. Intense green and red emissions were detected from the upconversion process for all the samples after excitation at 980 nm. The relative intensities of the emission bands around 550 nm and 665 nm, assigned to the H-2(11/2) -> I-4(15/2), S-4(3/2) -> I-4(15/2), and F-4(9/2) -> I-4(15/2) transitions, depended on the tantalum oxide content and the power of the laser source at 980 nm. The upconversion dynamics were investigated as a function of the Ta2O5 content and the number of photons involved in each emission process. Based on the upconversion emission spectra and 1931CIE chromaticity diagram, it is shown that color can be tailored by composition and pump power. The glass ceramic films are attractive materials for application in upconversion lasers and near infrared-to-visible upconverters in solar cells.